Program for Reducing Obesity (PRO): An institutional review of an insurance‐based weight loss program utilizing shared medical appointments - Jeffrey Wei; Lei Lei; Albert Shieh; Deepashree Gupta; Susan Ahern; Na Shen (Wiley, 2022)
Abstract Background Based on CDC estimates in the United States, the prevalence of obesity was 42.4% in 2017-2018, and the annual cost of obesity was $147 billion in 2008. Yet studies estimate that only 20-40% of adults with obesity received counseling from their primary care providers. Recent studies using shared medical appointments (SMA), where patients are seen by a multidisciplinary team, have shown promising results in obesity management. We developed an insurance‐based weight loss program incorporating SMA, called the Program for Reducing Obesity (PRO), and report our findings here. Methods Enrollment began in January 2019 at the UCLA Health Thousand Oaks clinic. Patients age ≥18 years with BMI ≥30 kg/m2 were eligible by referral to PRO, a program consisting of individual visits and SMAs with an obesity medicine board certified endocrinologist and registered dietitian. Primary outcomes were change in weight after 3, 6, and 12 months. Secondary outcomes included proportion that achieved ≥5% weight loss, change in percent body fat, HbA1c, HDL, triglycerides, and blood pressure. Results 102 patients (mean age 59.7 years, 72% women, mean weight 103.6 kg, mean BMI 36.6 kg/m2) have been analyzed, with 91 patients completing at least 12 months of the program. Patients achieved significant weight loss: 3.0%, 5.0%, and 7.8% of their baseline weight after 3, 6, and 12 months respectively. 52% of patients lost ≥5% of their baseline weight after 12 months. Patients had significant reductions in body fat: 2.1%, 7.4%, and 6.7% of their baseline (all p ≤ 0.01) after 3, 6, and 12 months respectively. Improvements were also seen in HbA1c (p ≤ 0.01), triglycerides (p ≤ 0.04), and systolic blood pressure (p ≤ 0.07) after 12 months although not all results achieved statistical significance. Conclusion Our institutional review of PRO, an insurance‐based obesity program utilizing SMA, demonstrates a successful approach to promoting weight loss in a community‐based setting.